PERMOHONAN HAK MILIK YANG BERASAL DARI TANAH NEGARA DI KANTOR PERTANAHAN KOTA SEMARANG - Ilham Ilham; Djauhari Djauhari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The basic foundation for the government and the people of Indonesia to formulate the politics of law and the policy of land affairs has been contained in the 1945 Constitution of the Republic of Indonesia Article 33 paragraph (3) which